Parity Democracy - Aldeguer Cerdá, Bernabé (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The concept of parity democracy has acquired a crescent presence in gender and politics studies during the last four decades. This concept serves as a political and juridical reference for positive discrimination strategies incorporated in several political areas (family conciliation, labour law, academical and professional training). Among these dimensions highlights the electoral system as an institutional variable linked to political representation of women. In this process, the international research agenda, as well as recommendations and reports issued by several international organizations, have influenced the discourses that have pursued to political parties, parliaments and cabinets to the development of strategies for the success of parity. The most presence of women in parliaments is not without persistent obstacles that, in both formal and informal way, prevent their real and effective participation in every political making – decisions. It can be observed by the differentiated presence of women and men, as MPs, in parliamentary committees or cabinets according with the portfolio (horizontal discrimination) or considering the positions (vertical discrimination). The study of parity democracy is related to the democratic strengthening strategies. At the same time, considering the complexity of the several factors that affect to gender discrimination, the explicative variables have been grouped in institutional, ideological-cultural and socioeconomical factors. Electoral quotas are adopted by several types which analysis requires, currently, a research agenda directed to evaluate the real impact that these gender measures have had over the equal political participation between men and women.
Keywords: democracy; equality; positive discrimination; parity; quotas